2018
DOI: 10.1002/jcla.22592
|View full text |Cite
|
Sign up to set email alerts
|

GJB3/GJB6 screening in GJB2 carriers with idiopathic hearing loss: Is it necessary?

Abstract: GJB3/GJB6 variants account for a low proportion in autosomal recessive GJB2 mutation carriers in our cohort. Environmental causes, or other NSHI relevant genes, revealed by targeted next generation sequencing or whole exome sequencing, may play major roles in triggering deafness in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 29 publications
(91 reference statements)
0
9
0
Order By: Relevance
“…However, digenic mutations have also been reported recently [7][8][9][10][11][12]. In our cases, the compound heterozygous for GJB2 variants (p.V37I ) and MYO7A (p.L347I) variant were found in the proband using whole-exome sequencing.…”
Section: Discussionmentioning
confidence: 48%
See 2 more Smart Citations
“…However, digenic mutations have also been reported recently [7][8][9][10][11][12]. In our cases, the compound heterozygous for GJB2 variants (p.V37I ) and MYO7A (p.L347I) variant were found in the proband using whole-exome sequencing.…”
Section: Discussionmentioning
confidence: 48%
“…In 2009, Liu et al [8] identi ed heterozygous GJB2 and GJB3 mutations in NHSL patients. Since then, many other digenic inheritance has been reported [7][8][9][10][11][12], such as GJB2/GJB3, GJB2/MITF, and GJB2/ TMPRSS3 (Table 1). Although the digenic inheritance has been increasingly described in NSHL, the prevalence is unknown.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most NSHL forms are monogenic and have genetic heterogeneity. However, digenic/oligogenic inheritance has been reported recently [4-9]. Here, the novel compounds heterozygous for the GJB2 p.V37I variant and MYO7A p.L347I variant were found in the proband.…”
Section: Discussionmentioning
confidence: 78%
“…In 2009, Liu et al [5] have identified heterozygous GJB2 and GJB3 mutations in patients with NSHL. Since then, many other forms of digenic inheritance have been reported [4-9], such as GJB2/GJB3 , GJB2/MITF , and GJB2/TMPRSS3 (Table 1). Although digenic inheritance has been increasingly described in NSHL, its prevalence is unknown.…”
Section: Discussionmentioning
confidence: 99%